Analysis Of Strategy For Implementing Operational Service Processes To Enhance Customer Satisfaction (PT. Bank Syariah Indonesia TBK KCP Tangerang Cikupa 1) - Ilyas, Fadli; Sari, Risma Puspita (Jurnal Multidisiplin Sahombu, 2025)
The rapid development of technology has driven the need for fast and efficient services in business activities, including in financial institutions like Islamic banks. This study aims to analyze customer satisfaction with the operational services of PT. Bank Syariah Indonesia KCP Tangerang Cikupa 1. Through a three-month Field Work Practice (PKL) program in the Frontliner section, the researcher observed challenges in the operational service processes, including long queues, customer confusion, and incomplete documentation. Based on these observations, several solutions were proposed, such as increasing operational staff, providing better guidance for customers, and ensuring the completeness of required documents. These recommendations aim to enhance service quality and customer satisfaction. The findings contribute valuable insights into the operational service processes of Islamic banks, particularly in addressing customer concerns and improving service efficiency